STRATEGI PENGEMBANGAN BISNIS DALAM UPAYA PENINGKATAN VOLUME PENJUALAN PADA PRIMA RATU CATERING PURWAKARTA - Haifa Ilma Amala, - (2021)
The purpose of this research is to analyze and describe internal factors and external factors that can affect the determination of business development strategies at Prima Ratu Catering. The methodology used is descriptive quantitative using interviews and questionnaires to be analyzed using SWOT analysis. Based on the results of the SWOT analysis, Prima Ratu Catering has 7 strengths, 3 weaknesses, 4 opportunities and 4 threats. Analyzed using the IFE Matrix with a total score of 2.68, the EFE Matrix of 2.76, the position of the IE Matrix in cell V, namely Growth & Stability and resulted in 6 alternative strategies for Prima Ratu Catering to develop its business in an effort to increase sales volume. Keywords: Development strategy; SWOT analysis; EFE Matrix; IFE Matrix; IEMatrix; QSPM